Optogenetic stimulation of astrocytes causes an overall inhibitory effect in the hippocampal CA1 - Theint, Aye Theint (Nanyang Technological University, 2021)
As optogenetics offers a promising strategy in treating pathological conditions, optogenetic application in astrocytes could be a better alternative intervention because it bypasses direct manipulation of neurons. Optogenetic stimulation of astrocytes through channelrhodopsin-2 has been used in neuroscience with the findings that neuronal activity was regulated by optogenetics stimulation of astrocytes. Different studies have shown different effects of optogenetic stimulation of astrocytes. A recent study has shown that optogenetic stimulation of astrocytes results in an increased extracellular K+ concentration (Octeau et al., 2019), increasing firing rates of neurons. In contrast, some studies have suggested that optogenetic stimulation inhibits pyramidal cells activity in the hippocampal slices (Tan et al., 2017). These contradictory findings form the research question – what is the effect of optogenetic stimulation of astrocytes in regulating neuronal activity in the hippocampal CA1 in vivo. To answer the question, we aim to understand how neuronal activity in hippocampal CA1 of mice in vivo is regulated by optogenetic stimulation of astrocytes. This understanding is important for the potential application of optogenetic stimulation of astrocytes as a potential therapeutic strategy. In this study, I have established an optogenetic approach to specifically target astrocytes. Using this optogenetic stimulation method, we have shown that light stimulation of astrocytes induces the activity of some neurons in the hippocampal CA1 while toning down other neuronal population with a delay. Light stimulation of astrocytes through CatCh caused an overall inhibitory effect, probably through activation of interneurons in the hippocampal CA1 area. Based on this finding, our work serves as a platform for application of light stimulation of astrocytes in treating pathological conditions such as epilepsy.